Biointegration of corneal macroporous membranes based on poly(ethyl acrylate) copolymers in an experimental animal model. Issue 3 (18th June 2014) - Alió del Barrio, Jorge L.; Chiesa, Massimo; Gallego Ferrer, Gloria; Garagorri, Nerea; Briz, Nerea; Fernandez‐Delgado, Jorge; Sancho‐Tello Valls, Maria; Botella, Carmen Carda; García‐Tuñón, Ignacio; Bataille, Laurent; Rodriguez, Alejandra; Arnalich‐Montiel, Francisco; et al.
Abstract Currently available keratoprosthesis models (nonbiological corneal substitutes) have a less than 75% graft survival rate at 2 years. We aimed at developing a model for keratoprosthesis based on the use of poly(ethyl acrylate) (PEA)‐based copolymers, extracellular matrix‐protein coating and colonization with adipose‐derived mesenchymal stem cells. Human adipose tissue derived mesenchymal stem cells (h‐ADASC) colonization efficiency of seven PEA‐based copolymers in combination with four extracellular matrix coatings were evaluated in vitro. Then, macroporous membranes composed of the optimal PEA subtypes and coating proteins were implanted inside rabbit cornea. After a 3‐month follow‐up, the animals were euthanized, and the clinical and histological biointegration of the implanted material were assessed. h‐ADASC adhered and survived when cultured in all PEA‐based macroporous membranes. The addition of high hydrophilicity to PEA membranes decreased h‐ADASC colonization in vitro. PEA‐based copolymer containing 10% hydroxyethyl acrylate (PEA‐HEA10) or 10% acrylic acid (PEA‐AAc10) monomeric units showed the best cellular colonization rates. Collagen plus keratan sulfate‐coated polymers demonstrated enhanced cellular colonization respect to fibronectin, collagen, or uncoated PEAs. In vivo implantation of membranes resulted in an extrusion rate of 72% for PEA, 50% for PEA‐AAc10, but remarkably of 0% for PEA‐HEA10. h‐ADASC survival was demonstrated in all the membranes after 3 months follow‐up. A slight reduction in the extrusion rate of h‐ADASC colonized materials was observed. No significant differences between the groups with and without h‐ADASC were detected respect to transparency or neovascularization. We propose PEA with low hydroxylation as a scaffold for the anchoring ring of future keratoprosthesis. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1106–1118, 2015.